Emergência e significado da 'participação' do trabalhador na empresa capitalista - Santana, Denia Glais (1994)
This dissertation concems the analysis of the rising of a participative management in the contemporary work processo Starting from conceptual formulations from Karl Marx's alienation theory, and initiatly focusing more often the alienation implicated in the act which executes work, one find, in a first instance, to accompany several phases of capitalist work process which has succeeded in history. After, is reconsidered the introduction and the development of social sciences in the study of the force of work behavior to relate the influence of concepts that come from that on the construction of participative models which are used in the work processes management which are drawn today. One conclude, finally, pointing to the meaning that this participation acquires, in a sense of alienation implicated in a work process whose final purpose is determinated, a priori, independently from workers' will.